Implementation of the Speakia Application for Junior High School : Student’ Point of View - Nabila Irsani; Benni Ichsanda Rahman Hz (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study explores the implementation of the Speakia application in enhancing English vocabulary among junior high school students from their perspective. Technological advancements have significantly influenced language learning, making it more interactive and accessible. The Speakia app, used by over fifty million users since 2021, offers a virtual environment for practicing English through immersive daily activities. This research aims to evaluate the effectiveness of Speakia in improving vocabulary, its advantages, disadvantages, and the motivational impact on students. A qualitative case study methodology was employed, involving 25 purposively selected junior high school students. Data was collected through adapted questionnaires and semi-structured interviews. Quantitative analysis of the questionnaires provided insights into students' perceptions, while qualitative analysis of interviews offered an in-depth understanding of their experiences. Results indicate that students generally find Speakia easy to use and effective in enhancing vocabulary. The app's interactive features, quizzes, and real-time pronunciation feedback are highly appreciated. However, challenges such as the need for premium accounts for advanced levels and reliable internet access were noted as significant barriers. Despite these drawbacks, students reported increased motivation and active engagement in learning English through the app.